A light-weight scalable truthful routing protocol in MANETs with selfish nodes. (9th April 2009) - Wang, Yongwei; Singhal, Mukesh
We introduce a Light-weight Scalable Truthful rOuting Protocol (LSTOP) for selfish nodes problem in mobile ad hoc networks where a node may use different cost to send packets to different neighbours. LSTOP encourages nodes' cooperation by rewarding nodes for their forwarding service according to their cost. It incurs a low overhead of O(n 2) in the worst case and only O(n) on the average. We show the truthfulness of LSTOP and present the result of an extensive simulation study to show that LSTOP approaches optimal (cost) routing and achieves significant better network performance compared to ad hoc-VCG.